Application of ATP-based bioluminescence for bioaerosol quantification: Effect of sampling method. (December 2015) - Han, Taewon; Wren, Melody; DuBois, Kelsey; Therkorn, Jennifer; Mainelis, Gediminas
Abstract: An adenosine triphosphate (ATP)-based bioluminescence has potential to offer a quick and affordable method for quantifying bioaerosol samples. Here we report on our investigation into how different bioaerosol aerosolization parameters and sampling methods affect bioluminescence output per bacterium, and implications of that effect for bioaerosol research. Bacillus atrophaeus and Pseudomonas fluorescens bacteria were aerosolized by using a Collison nebulizer (BGI Inc., Waltham, MA) with a glass or polycarbonate jar and then collected for 15 and 60 min with: (1) Button Aerosol Sampler (SKC Inc., Eighty Four, PA) with polycarbonate, PTFE, and cellulose nitrate filters, (2) BioSampler (SKC Inc.) with 5 and 20 mL of collection liquid, and (3) our newly developed Electrostatic Precipitator with Superhydrophobic Surface (EPSS). For all aerosolization and sampling parameters we compared the ATP bioluminescence output per bacterium relative to that before aerosolization and sampling. In addition, we also determined the ATP reagent storage and preparation conditions that do not affect the bioluminescence signal intensity. Our results show that aerosolization by a Collison nebulizer with a polycarbonate jar yields higher bioluminescence output per bacterium compared to the glass jar. Interestingly enough, the bioluminescence output by P. fluorescens increased substantially after its aerosolization compared to the fresh liquid suspension. For both test microorganisms, the bioluminescence intensity per bacterium after sampling was significantly lower than that before sampling suggesting negative effect of sampling stress on bioluminescence output. The decrease in bioluminescence intensity was more pronounces for longer sampling times and significantly and substantially depended on the sampling method. Among the investigated method, the EPSS was the least injurious for both microorganisms and sampling times. While the ATP-based bioluminescence offers a quick bioaerosol sample analysis method, this works demonstrates that the method output depends on bioaerosol generation and sampling methods, as well as reagent storage. Highlights: Various factors affecting the ATP bioluminescence intensity were investigated. Optimal conditions for the ATP reagent storage and preparation determined. The bioluminescence intensity was significantly affected by mechanical stress. The bioluminescence intensity significantly depended on sampling method. Electrostatic sampler was least injurious to bacteria among investigated samplers.